Avaliação de projetos sociais: análise da metodologia utilizada pela Petrobrás - Montenegro Filho, Mário Jorge França (2013)
On the aggravation of social problems and the shortage of resources, the improvement of evaluation methods and control of its application, requiring more efficiency, efficacy, effectiveness and participation in its management, has been growing. As a result, emerges the importance of studying and developing such methodologies. The overall goal of this dissertation is to know what are the difficults to incorporate the point of view of executers and beneficiaries in evaluation process. To do so, has been done a research characterized as qualitative, with a field strategy using the case study of two social projects called Petrobras Child Program, situated in the metropolitan region of Natal, and Content Analysis technique for analyze the data. The conclusions of this work can assist in improving the process of projects evaluation financed by Petrobras, contributing with its social role, besides the possibility of encouraging a greater participation of other society actors, such as beneficiaries, in the evaluation process